Cobalamin and Folic Acid Status in Relation to the Etiopathogenesis of Pancytopenia in Adults at a Tertiary Care Centre in North India - M. Premkumar; N. Gupta; T. Singh; T. Velpandian (Anemia)
Background. Pancytopenia has multiple etiologies like megaloblastic anemia, aplastic anemia, leukemia, and various infections. We investigated the clinical, etiological and hematological profile including bone marrow morphology of patients with pancytopenia in relation to their vitamin B12 and folic acid status at a tertiary care referral hospital in north India. Methods. A total of 140 consecutive patients with pancytopenia were selected from June 2007 to December 2008. Bone marrow examination and other tests were carried out as warranted, including serum cobalamin and folate assays using liquid chromatography mass spectroscopy (LC MS/MS). Results. The study population consisted of 92 males and 48 females with a mean age of 32.8 years. Megaloblastic anemia 60.7%, aplastic anemia (7.8%), and leukemia (9.2%) were common causes. Infectious causes (16.4% of all cases) included leishmaniasis, HIV–AIDS, malaria and tuberculosis. Severe cobalamin deficiency (B12 < 100 pg/mL) was seen in 81% of all patients including 91.6% of patients with MA. In contrast, only 7.14% of all pancytopenic patients were folate deficient. Folate deficiency (<5 ng/mL) was seen in just 5% MA patients. Combined cobalamin and folate deficiency was seen in 5 patients (3.51%). Conclusion. Cobalamin deficiency was found to be more common in our setting and is largely underdiagnosed in the age of folate supplementation. Infectious diseases like tuberculosis, leishmaniasis, and increasingly HIV are important and treatable causes of pancytopenia. This is in contrast with the developed nations where the bulk of disease is due to malignancy or marrow aplasia.